Influence of the electroneutrality of a metal layer on the plasmon spectrum in dielectric–metal–dielectric structures - Kostrobij P. P.; Markovych B. M.; Polovyi V. Ye.; Костробiй П. П.; Маркович Б. М.; Польовий В. Є. (Lviv Politechnic Publishing House, 2019)
In this paper, we propose a model that allows us to investigate the influence of quantum size effects and the electroneutrality condition on the spectrum of SPPs waves as a function of metal thickness in heterogeneous dielectric/metal/dielectric structures. It is shown that for ultrathin metal layers, the spectrum of plasmon waves has oscillatory behavior in the domain of small wave vectors (k ≈ 0.05−0.2 nm−1). The amplitude of oscillations depends on the conditions of electroneutrality for the dielectric/metal/dielectric structure. surface plasmon, plasmon spectrum, metal layer thickness, dielectric permittivity, electroneutrality. У роботi запропоновано модель, яка дає змогу дослiдити вплив квантоворозмiрних ефектiв та умови електронейтральностi на спектр SPPs хвиль як функцiї товщини металу в гетерогенних структурах “дiелектрик–метал–дiелектрик”. Показано, що для надтонких металевих прошаркiв спектр плазмонних хвиль проявляє осциляцiйну поведiнку в областi малих хвильових векторiв (k ≈ 0.05 − 0.2 нм−1). Амплiтуда осциляцiй залежить вiд умов електронейтральностi для структури “дiелектрик–метал–дiелектрик”.
Вплив електронейтральностi металевого прошарку на плазмонний спектр у структурах “дiелектрик–метал–дiелектрик”
Keywords: surface plasmon, plasmon spectrum, metal layer thickness, dielectric permittivity, electroneutrality, поверхневий плазмон, спектр плазмона, товщина металевого шару, дiелектрична проникнiсть, електронейтральнiсть